Strengthening ecoliteracy through eco comic in peat conservation efforts in Kampung Jati Baru Siak - Viony Syafitra; Wilasari Arien; Desi Yusnita Mailinda; Lutfiana Arbiah; Masyitha Ramadhani; Ningrum Melihayatri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Environmental education plays an important role in developing ecological literacy among primary school students, particularly in regions characterized by unique local ecosystems. However, environmental learning materials often remain disconnected from students’ everyday environmental experiences. This study aimed to evaluate the implementation of the Eco Comic program as a contextual learning medium for strengthening ecological literacy related to peatland conservation among primary school students in Kampung Jati Baru, Siak Regency, Riau Province, Indonesia. The study employed a descriptive qualitative approach with a program evaluation design. Data were collected through observations, interviews, documentation, and learning evaluations involving students, teachers, environmental practitioners, illustrators, and village officials. An initial needs assessment involving 30 students was conducted to identify students’ prior understanding of peatland ecosystems, while the implementation stage involved 65 students from three elementary schools. The findings revealed that the Eco Comic program was implemented through four interconnected stages: planning, organizing, implementation, and evaluation. During the planning stage, peatland-related environmental issues were integrated into comic narratives that were familiar to students. The study highlights the potential of locally contextualized comic-based learning media to support the development of ecological literacy and strengthen environmental education in primary schools. These findings contribute to environmental education literature by demonstrating how local peatland ecosystem knowledge can be integrated into visual learning media for young learners.